COMPARATIVE ANALYSIS TO WEDDINGS OF VALLEY AND OASIS - Abduganiev Shukurullo (Academia Science Repository, 2023)
The article is based on a comparative analysis of the traditions and ceremonies of valley and oasis weddings (weddings of Fergana and Bukhara), dishes prepared at the wedding, clothes worn and their unique aspects using methodological methods, scientific analysis of the literature on this topic.